Bank Balance Sheets and the Value of Lending - Chen, Jiaqian; Vera, Giuseppe (Washington, D.C. : International Monetary Fund, 2017)
We study 1,400 UK syndicated loans, together with the financial history of the lead bank and the borrowing firm. We interpret abnormal equity returns around loan announcements as the value of the lending relationship to the firm. We find that: (i) Consistent with previous evidence, the value of lending is higher when the firm is riskier or more opaque, suggesting that it primarily reflects the lead bank's screening and monitoring activities. (ii) As a bank becomes larger, more profitable or more capitalized, the value of its loans first increases and then decreases. The largest, most capitalised or most profitable banks do not give the most valuable loans. (iii) Firms which receive low-value loans are more likely to experience low profitability and financial distress during the lending relationship. By relating the state of bank balance sheets to borrower performance, we offer a new angle to evaluate the impact of financial conditions on the real economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet